Possibilities for the Application of Low-Temperature Argon Plasma in the Treatment of Postoperative and Long-Term Non-Healing Wounds - S. A. Frolov; A. M. Kuzminov; D. V. Vyshegorodtsev; V. Yu. Korolik; N. V. Tuktagulov; M. A. Sukhina; I. A. Mukhin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To review available information on the use of low-temperature argon plasma in the treatment of postoperative and long-term non-healing wounds.General findings. Low-temperature argon plasma is an ionised gas, one of the four classical aggregate states of matter. Its therapeutic effect is achieved by means of the gas-dynamic effect, i.e. an argon flow with a high heat content and wide-spectrum recombination radiation — from the vacuum ultraviolet region to the near infrared range, as well as by means of the pronounced catalytic properties of gaseous argon, which is important for a number of biochemical reactions. Low-temperature argon plasma has a pronounced antibacterial effect. In a number of studies, the wound healing effect of low-temperature argon plasma was demonstrated.Conclusion. The use of low-temperature argon plasma can reduce the time of wound healing, the titre of clinically significant microorganisms and the time spent by patients in hospital. In addition, the use of low-temperature argon plasma can improve patients’ quality of life in the postoperative period.